Colonialism on the cheap: The French empire 1830-1962 - Denis Cogneau; Yannick Dupraz; Elise Huillery; Sandrine Mesplé-Somps (African Economic History Network (AEHN), 2024)
How much did France pay for its colonial empire? Did colonies benefit from large transfers from French taxpayers and private investors, or were they on the contrary drained of their capital? So far, Jacques Marseille (1984) was the only attempt to investigate these questions, by deducting from the structural trade deficit of the French colonies that they were a heavy financial burden for France. We collect novel budgetary and loan data from archives and compute public monetary flows between France and the colonies between 1833 and 1962. We also provide figures of colonial private investment through the Paris Stock Exchange. Public expenditure spent by France on the empire only represented 1.3% of its GDP, of which four fifths were in the military. The persistent trade balance deficits of French colonies did not correspond to large public or private capital transfers, as they were in fact counterbalanced by military expenditure from the Metropole. Once accounting for this, the colonial drain of the French empire is comparable to British India.
Keywords: 330; French colonial Empire; Public expenditures; Public Finance; Public revenue; Trade Balance